Effect of ultrashort laser-induced surface flaws on architectural glass strength. (9th August 2021) - Nategh, Shahryar; Missinne, Jeroen; Vijverman, Pieter; Van Steenberge, Geert; Belis, Jan
Highlights: Systematic guideline on the laser parameter optimization is given. Realizing well-controlled surface flaws on architectural glass is achievable. Realized flaws had depths in the range of 42–123 μm on a 4 mm thick glass. No cracks/chippings were observed around/underneath the artificial flaws. Standard deviations in the strength values were less than 1 MPa. Abstract: The present study gives a new insight into the use of laser ablation technology as a robust tool for fracture mechanical and strength examination of scratched architectural glass (soda-lime silica glass). Previously, mechanical tools such as indenters have been used for this purpose; however, artificial scratches produced with such instruments are accompanied by cracks and chippings, which degrade the accuracy of the results. Here, an ultra-short laser with picosecond pulse duration is employed to achieve highly controlled artificially applied flaws. Since most research on laser ablation has been done in the field of optics and electronics and is focused on non-structural/architectural glass, e.g. borosilicate, aluminosilicate, and fused silica, there is no detailed study on laser parameter optimization of soda-lime silica glass. Therefore, laser parameters have been optimized in view of achieving minimal cracks and chippings, along the laser-ablated flaw. The artificial flaws were thoroughly characterized in terms of depth, edge quality and reproducibility using several microscope inspection techniques. Subsequently, highly accurate laser-induced artificial flaws in the range of 42 μm to 123 μm were realized and four-point bending tests were performed to assess the impact of flaw depths on the glass strength and to illustrate the accuracy of the method. Remarkably low standard deviations of the strength values for the laser-modified (LM) specimens were obtained. It is shown that 81 μm difference between the maximum and minimum laser-induced flaw depths results in a glass strength difference of 41.4%. This well-controlled modification of architectural glass can pave the way for further surface modifications applicable to building industry and help in experimentally validating fracture mechanic theories.